THE ROLE OF VITAMIN B12 IN THE DEVELOPMENT OF HYPERANDROGENISM AND METHODS TO IMPROVE MODERN TREATMENT APPROACHES - Ashurova Nigora Gafurovna; Najimova Sumanbar Tulkinovna (World Scientific Research Journal, 2025)
Hyperandrogenism is a clinical syndrome characterized by excessive production of androgen hormones in women, leading to various gynecological and endocrine disorders. Recent studies have highlighted the critical roles of vitamin B12 in metabolism, hormonal balance, and nervous system functioning. This article analyzes the pathogenesis of hyperandrogenism and the potential involvement of vitamin B12 in its development. Additionally, contemporary treatment methods are reviewed, with a focus on the role of vitamin B12 supplementation in enhancing therapeutic efficacy.